Uji Aktivitas Ekstrak Etanol Bunga Kembang Sepatu (Hibiscus rosasinensis L.) Terhadap Motilitas Sperma Mencit Jantan (Mus musculus) - Rani Melyandari, Abd. Halim Umar, Radhia Riski , Mirnawati Salampe (STIFA Makassar, 2016)
Hibiscus rosa-sinensis L. is a plant suspected to have affect the motility of sperms. This research aims to know the effect of Hibiscus rosa-sinensis L. in motility of sperms as well as to get information about the dose of ethanol extract of this plant having activity in motility of sperms male mice. The animals were divided into 4 groups according to the dose administered to each group i.e 10 mg/20 g mice, 25 mg/20 g mice, 50 mg/20 g mice and control, respectively. The treatments were conducted for 10 days where each treatment group had 3 replication. The animals were then dissected and cement fluid located in vas deferens was collected. The motility of sperms was observed under microscope. Based on the results analyzed by statistical analysis showed that ethanol extract of Hibiscus rosa-sinensis L. to have affect the motility of sperms at dose 50 mg/20 g mice and gives significantly different result compared to negative control.